Koens, Lyndon - (:unkn) unknown (My University, 2026)
Dr Koens' research explores the dynamics of microscopic objects in fluids. This research aims to improve our understanding of bacterial swimming, colloids, active matter and the dynamics of micro-machines. At these small scales motion critically depends on an objects shape and the interactions with its neighbours. Dr. Koens employs analytical approximations and simple numerical techniques to explore the effect of geometry on dynamics and to develop simple models for recent experimental systems. These models then help develop and optimize artificial micromachines